Sistem Absensi Karyawan Berbasis Web Dengan Menggunakan Teknologi Radio Frequency Indentification (RFID) - Rosmiati, Rosmiati; Isnur, Muhammad Iqbal; Baharudin, Baharudin (Patria Artha Technological Journal, 2021)
Attendance is a mandatory requirement for employee attendance. There are still many who use the manual system. Of course it is not efficient, so an attendance attendance system is needed that can run to facilitate attendance tasks and activities. Attendance management is one of the systems that is currently very much needed along with the large number of human populations that must be recorded. However, most of the attendance systems currently used are still using conventional methods such as signatures to fill attendance in this way, so there are lots of loopholes for fraud that often occur. By utilizing a tool using a microcontroller. This system uses RFID RC 522 as a tool and programming language for PHP and SQL server for database management. This system uses the blackbox testing method to find out the website designed to function correctly employee attendance information technology with employee ID card documents as a website-based system there are facilities such as employee data management, room data management, attendance data management, and monthly attendance processing using cards. employee identity. It can be concluded that by using this website, the attendance process will be more efficient and can be easily monitored by leaders and the center.